2016
DOI: 10.1080/15384047.2016.1219815
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes secreted from human colon cancer cells influence the adhesion of neighboring metastatic cells: Role of microRNA-210

Abstract: Cancer-secreted exosomes influence tumor microenvironment and support cancer growth and metastasis. MiR-210 is frequently up-regulated in colorectal cancer tissues and correlates with metastatic disease. We investigated whether exosomes are actively released by HCT-8 colon cancer cells, the role of exosomal miR-210 in the cross-talk between primary cancer cells and neighboring metastatic cells and its contribution in regulating epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 29 publications
3
70
0
Order By: Relevance
“…Higher Mir-210 levels were also reported to enhance invasion and metastasis in cell lines (Mudduluru et al 2015) . We did not observe up-regulation of Mir-210_3p in pCRC compared to nCR; rather, our results show up-regulation at the metastatic sites, which is in accordance with several non-NGS studies in CRC [68][69][70] . Our finding of increased Mir-210_3p expression at all mCRC sites, suggest that hypoxic stress is a common occurrence at the metastatic sites, and that up-regulation of Mir-210_3p may be a consequence of this hypoxic microenvironment.…”
Section: Mir-210supporting
confidence: 92%
“…Higher Mir-210 levels were also reported to enhance invasion and metastasis in cell lines (Mudduluru et al 2015) . We did not observe up-regulation of Mir-210_3p in pCRC compared to nCR; rather, our results show up-regulation at the metastatic sites, which is in accordance with several non-NGS studies in CRC [68][69][70] . Our finding of increased Mir-210_3p expression at all mCRC sites, suggest that hypoxic stress is a common occurrence at the metastatic sites, and that up-regulation of Mir-210_3p may be a consequence of this hypoxic microenvironment.…”
Section: Mir-210supporting
confidence: 92%
“…For example, exosomes derived from breast cancer cells can transmit miRNAs to normal recipient cells to induce their malignant transformation (Li, Ren, Tang, & Yu, 2017). Exosomes secreted by human colon cancer cells can transmit miR-210 to neighboring metastatic cells to influence their adhesion (Bigagli, Luceri, Guasti, & Cinci, 2016). Similarly, exosome-transmitted long ncRNA PTENP1 participates in normal-cell-to-bladder-cell communication during the carcinogenesis of bladder cancer (Zheng et al, 2018).…”
Section: Mir-221 Of Exosomes Derived From 16hbe-t Promotes Cell Viamentioning
confidence: 99%
“…In other words, miR‐215 could be used as a potential therapeutic target for prevention of metastasis and also as a new main biomarker in the pathogenesis of CRC . In contrast, a study on HCT‐8 cell line has shown that miR‐210 was upregulated in exosomes derived from these cells and this miRNA resulted in cancer cell metastasis and homing processes (Table ). Furthermore, it is shown that exosomal CRNDE‐h lncRNA levels in patients with CRC were higher and it was positively associated with distant metastasis and especially regional lymph node metastasis (Table ) …”
Section: Exosomes In Crc Metastasismentioning
confidence: 99%